ANALYSIS OF LABOR AND LEISURE PRACTICES OF SHADOW SELF-EMPLOYED IN THE PHYSICAL LABOR MARKET IN RUSSIA - I. A. Yurasov; M. A. Tanina; V. A. Yudina; E. V. Kuznetsova (Вестник университета)
Blue-collar self-employment occupies about 23 – 25 % in the structure of the Russian economy and is the most difficult for sociological analysis due to its isolation from the outside world. The most acceptable methods of sociological analysis of the self-employed in the field of physical labor are observation, observation is included, an unstructured interview in a relaxed atmosphere, since they are very closed and careful, understanding the secrecy and illegality of their employment. The blue-collar self-employed demonstrate a specific “kulak” mentality that combines hard work, social flexibility, a low horizon for strategic planning of personal and work life, adventurism, mobility, self-exploitation, greed, mercantilism, and socio-cultural limitations. By their stratification nature, the blue-collar self-employed are reviving the archaic Russian urban class with its specific mentality, habits, and way of life. The blue-collar self-employed exhibit a hedonistic, prestigious form of consumption. Thanks to their income, they have made physical labor in the form of free self-employment very prestigious in the modern Russia.